Essentials of anatomy and physiology - Scanlon, Valerie C.; Sanders, Tina (Philadelphia, Pennsylvania : F. A. Davis Company, 2007)
Describes and illustrates the important aspects of anatomy, physiology, and pathophysiology.
Organization and general plan of the body -- Some basic chemistry -- Cells -- Tissues and membranes -- The integumentary system -- The skeletal system -- The muscular system -- The nervous system -- The senses -- The endocrine system -- Blood -- The heart -- The vascular system -- The lymphatic system and immunity -- The respiratory system -- The digestive system -- Body temperature and metabolism -- The urinary system -- Fluid-electrolyte and acid-base balance -- The reproductive systems -- Human development and genetics -- An introduction to microbiology and human disease.
Includes index.
Keywords: HUMAN ANATOMY